2010
DOI: 10.1097/ccm.0b013e3181eed90a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of continuous compressions and 30:2 cardiopulmonary resuscitation on global ventilation/perfusion values during resuscitation in a porcine model*

Abstract: In the first 12 mins of cardiopulmonary resuscitation, continuous compressions could maintain relatively better coronary perfusion pressure, Pao2, and global ventilation/perfusion values than 30:2 cardiopulmonary resuscitation. Therefore, rescue ventilation during 12 mins of simulated bystander cardiopulmonary resuscitation did not improve hemodynamics or outcomes compared with compression-only cardiopulmonary resuscitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 22 publications
2
30
0
2
Order By: Relevance
“…These results indicate that wholebody mild hypothermia reduced the MMP of brain cortex in the well-established VF-induced cardiac arrest model in swine. 3,26,27 Furthermore, at 24 hours after ROSC, whole-body mild hypothermia improved neurologic outcomes and alleviated microscopic and ultrastructural changes in the cerebral cortex caused by global ischemia-reperfusion, as described in our earlier paper. 3 However, at 72 hours after ROSC, NT and HT groups had similar histopathology 3 and cellular findings in the present experiment.…”
Section: Discussionmentioning
confidence: 97%
“…These results indicate that wholebody mild hypothermia reduced the MMP of brain cortex in the well-established VF-induced cardiac arrest model in swine. 3,26,27 Furthermore, at 24 hours after ROSC, whole-body mild hypothermia improved neurologic outcomes and alleviated microscopic and ultrastructural changes in the cerebral cortex caused by global ischemia-reperfusion, as described in our earlier paper. 3 However, at 72 hours after ROSC, NT and HT groups had similar histopathology 3 and cellular findings in the present experiment.…”
Section: Discussionmentioning
confidence: 97%
“…Our previous study also found that CC could maintain relatively better coronary perfusion pressure, PaO 2 , and global ventilation/perfusion values during CPR than VC (22). However, both groups with or without rescue breathing had similar 24-hr survivals and cerebral performance categories.…”
Section: Discussionmentioning
confidence: 76%
“…Die Beatmung spielt nach wie vor eine große Rolle im Ablauf des Reanimationsalgorithmus, wenngleich ihre Bedeutung in den ersten Minuten des Kreislaufstillstands in den vergangenen Jahren in Frage gestellt worden ist [19][20][21][22][23]. Relativ geringe Atemminutenvolumina scheinen ausreichend, um eine suffiziente Sauerstoffversorgung zu gewährleisten [12], während hohe Tidalvolumina das Risiko einer Magenblähung erhöhen und den Rückfluss venösen Bluts zum Herzen behindern können [13].…”
Section: Ablauf Des Reanimationsalgorithmus -Beatmung Und Thoraxkomprunclassified
“…In einer aktuellen Tierstudie konnte eine Verbesserung der Überlebensrate und ein verbessertes neurologisches Outcome in der CO-CPR-Gruppe gefunden werden [20]. Wang et al [21] zeigten, dass konventionelle CPR nicht mit einem verbesserten Outcome gegenüber CO-CPR in einem Tiermodell assoziiert war. Im Gegensatz hierzu konnte eine Observationsstudie in einem großen Patientenkollektiv keinen Vorteil der CO-CPR finden [22].…”
Section: » Die Beatmung Ist Nach Wie Vor Bedeutend Im Ablauf Des Reanunclassified